2021
DOI: 10.1093/glycob/cwab104
|View full text |Cite
|
Sign up to set email alerts
|

Sweet impersonators: Molecular mimicry of host glycans by bacteria

Abstract: All bacteria display surface-exposed glycans that can play an important role in their interaction with the host and in select cases mimic the glycans found on host cells, an event called molecular or glycan mimicry. In this review, we highlight the key bacteria that display human glycan mimicry and provide an overview of the involved glycan structures. We also discuss the general trends and outstanding questions associated with human glycan mimicry by bacteria. Finally, we provide an overview of several techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 148 publications
(203 reference statements)
0
19
0
Order By: Relevance
“…However, in case of host-microbe interactions, comprehending cell surface glycosylation and their biological functions extends not only to mammalian cells, but also to microbial glycans, as illustrated by the many glycan interactions between a host and microbe that influence processes like bacterial pathogenesis, interactions with host receptors, and sialylation to evade immune detection by mimicry of host glycans. [4,5] Currently, few glycoengineering techniques have been reported that can modify bacterial glycans. The most widely applied approach is metabolic oligosaccharide engineering (MOE), [6,7] which makes use of the cell's own metabolic pathways to incorporate monosaccharides with a chemical reporter group into sugar nucleotides that are eventually incorporated into bacterial glycans by native glycosyltransferases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in case of host-microbe interactions, comprehending cell surface glycosylation and their biological functions extends not only to mammalian cells, but also to microbial glycans, as illustrated by the many glycan interactions between a host and microbe that influence processes like bacterial pathogenesis, interactions with host receptors, and sialylation to evade immune detection by mimicry of host glycans. [4,5] Currently, few glycoengineering techniques have been reported that can modify bacterial glycans. The most widely applied approach is metabolic oligosaccharide engineering (MOE), [6,7] which makes use of the cell's own metabolic pathways to incorporate monosaccharides with a chemical reporter group into sugar nucleotides that are eventually incorporated into bacterial glycans by native glycosyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many of the reported glycoengineering techniques have focused on mammalian cells and have contributed to a better understanding of the structure‐function relationship of glycans within the context of the glycocalyx. However, in case of host‐microbe interactions, comprehending cell surface glycosylation and their biological functions extends not only to mammalian cells, but also to microbial glycans, as illustrated by the many glycan interactions between a host and microbe that influence processes like bacterial pathogenesis, interactions with host receptors, and sialylation to evade immune detection by mimicry of host glycans [4,5] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of sialidases directly impacts the level of sialic acid on cells, [4] allows the scavenging of sialic acid from other cells for use as an energy source [5] or is part of infection mechanisms of both viral and bacterial pathogens. [6] These various functions in health and disease, and the many different types of sialidases make this class of glycosidases an interesting target for study. The development of molecular tools that can perturb sialidase activity [7] and assist in their identification and quantification [8] is a key way to gain insight into their functional role(s).…”
Section: Introductionmentioning
confidence: 99%
“…Sialidases are the glycosyl hydrolase enzymes, also called glycosidases, responsible for cleaving sialic acids from the termini of glycans and are found in both vertebrates and various microbes. The activity of sialidases directly impacts the level of sialic acid on cells, [4] allows the scavenging of sialic acid from other cells for use as an energy source [5] or is part of infection mechanisms of both viral and bacterial pathogens [6] . These various functions in health and disease, and the many different types of sialidases make this class of glycosidases an interesting target for study.…”
Section: Introductionmentioning
confidence: 99%